Formal accounting planning in SMEs – the influence of family ownership and entrepreneurial orientation. Issue 3 (15th August 2016) - Samuelsson, Joachim; Andersén, Jim; Ljungkvist, Torbjörn; Jansson, Christian
Abstract : Purpose: Several studies have highlighted the importance of management accounting practices such as formal short-term planning and formal long-term planning for SME performance. However, few studies have considered what actually explains differences in the use of formal planning (from a management accounting approach) in SMEs. Family ownership and EO are two plausible explanations for such differences. The aim of this study is therefore to examine how family ownership and EO are correlated to the use of formal short-term planning and formal long-term planning in SMEs. Design/methodology/approach: In this study, we examined how family ownership and entrepreneurial orientation affect the use of formal planning by analyzing a sample of 156 Swedish manufacturing SMEs, using multivariate regression analysis. Findings: As could be expected, we were able to validate the notion that family firms use less formal planning than non-family firms. However, in contrast to some previous studies, we found that there is a strongly positive relationship between entrepreneurial orientation and the use of formal short-term planning and long-term planning. Originality/value: Whereas many previous studies on family business have assumed that family firms use less formal planning than non-family firms, the present study is one of few to actually confirm this notion. Also, this study has provided strong evidence that EO is positively correlated to the use of formal planning, in the short term and in the longer term.